Catalysis‐Independent ENPP1 Protein Signaling Regulates Mammalian Bone Mass. (29th July 2022) - Zimmerman, Kristin; Liu, Xiaochen; von Kroge, Simon; Stabach, Paul; Lester, Ethan R.; Chu, Emily Y.; Srivastava, Shivani; Somerman, Martha J.; Tommasini, Steven M.; Busse, Björn; Schinke, Thorsten; Carpenter, Thomas O.; et al.
ABSTRACT: Biallelic ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) deficiency induces vascular/soft tissue calcifications in generalized arterial calcification of infancy (GACI), and low bone mass with phosphate‐wasting rickets in GACI survivors (autosomal hypophosphatemic rickets type‐2). ENPP1 haploinsufficiency induces early‐onset osteoporosis and mild phosphate wasting in adults. Both conditions demonstrate the unusual combination of reduced accrual of skeletal mineral, yet excess and progressive heterotopic mineralization. ENPP1 is the only enzyme that generates extracellular pyrophosphate (PPi), a potent inhibitor of both bone and heterotopic mineralization. Life‐threatening vascular calcification in ENPP1 deficiency is due to decreased plasma PPi; however, the mechanism by which osteopenia results is not apparent from an understanding of the enzyme's catalytic activity. To probe for catalysis‐independent ENPP1 pathways regulating bone, we developed a murine model uncoupling ENPP1 protein signaling from ENPP1 catalysis, Enpp1 T238A mice. In contrast to Enpp1 asj mice, which lack ENPP1, Enpp1 T238A mice have normal trabecular bone microarchitecture and favorable biomechanical properties. However, both models demonstrate low plasma Pi and PPi, increased fibroblast growth factor 23 (FGF23), and by 23 weeks, osteomalacia demonstrating equivalent phosphate wasting in both models. Reflecting findings in whole bone, calvarial cell cultures from Enpp1 asj mice demonstrated markedly decreased calcification, elevated transcription of Sfrp1, and decreased nuclear β‐catenin signaling compared to wild‐type (WT) and Enpp1 T238A cultures. Finally, the decreased calcification and nuclear β‐catenin signaling observed in Enpp1 asj cultures was restored to WT levels by knockout of Sfrp1 . Collectively, our findings demonstrate that catalysis‐independent ENPP1 signaling pathways regulate bone mass via the expression of soluble Wnt inhibitors such as secreted frizzled‐related protein 1 (SFRP1), whereas catalysis dependent pathways regulate phosphate homeostasis through the regulation of plasma FGF23. © 2022 American Society for Bone and Mineral Research (ASBMR).